Mortality outcomes in patients receiving direct oral anticoagulants: a systematic review and meta‐analysis of randomized controlled trials. (5th October 2015) - Chai‐Adisaksopha, C.; Hillis, C.; Isayama, T.; Lim, W.; Iorio, A.; Crowther, M.
Summary: Background: Direct oral anticoagulants (DOACs) are widely used as an alternative for warfarin. However, the impact of DOACs on mortality outcomes compared with warfarin remains unclear. Objective: To estimate the mortality outcomes in patients treated with DOACs vs. warfarin (or another vitamin K antagonist). Methods: MEDLINE, EMBASE and CENTRAL databases (inception to September 2014), conference abstracts andwww.clinicaltrials.gov, were searched, without language restriction. Studies were selected if there were phase III, randomized trials comparing DOACs with warfarin in patients with non‐valvular atrial fibrillation or venous thromboembolism. Results: Thirteen randomized controlled trials involving 102 707 adult patients were included in the analysis. The case‐fatality rate of major bleeding was 7.57% (95% CI, 6.53–8.68; I 2 = 0%) in patients taking DOACs and 11.04% (95% CI, 9.16–13.07; I 2 = 33.3%) in patients taking warfarin. The rate of fatal bleeding in adult patients receiving DOACs was 0.16 per 100 patient‐years (95% CI, 0.12–0.20; I 2 = 36.5%). When compared with warfarin, DOACs were associated with significant reductions in fatal bleeding (RR, 0.53; 95% CI, 0.43–0.64; I 2 = 0%), cardiovascular mortality (RR, 0.88; 95% CI, 0.82–0.94; I 2 = 0%) and all‐cause mortality (RR, 0.91; 95% CI, 0.87–0.96; I 2 = 0%). Conclusions: The use of DOACs compared with warfarin is associated with a lower rate of fatal bleeding, case‐fatality rate of major bleeding, cardiovascular mortality and all‐cause mortality.